Teachers Assessment Practices and Their Influence on Pupils Learning Outcomes: Inputs for Designing Learning Exemplar - Denura, Ma. Laurene C. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the teachers’ assessment practices and their influence on pupils’ learning competencies as basis for designing learning exemplar. A descriptive research design was employed, focusing on all seven teachers of Rombang Elementary School through total enumeration sampling. A researcher-made questionnaire was used to gather the needed data on teachers’ assessment practices and pupils’ competency levels using a 5-point Likert scale. Descriptive statistics, particularly percentages and weighted mean were utilized to determine the levels of assessment practices and learning competencies. Data gathered revealed that the respondents frequently implemented formative assessment practices and consistently applied summative assessment practices. Likewise, pupils’ learning competencies were rated high, particularly in literacy and numeracy skills, application of learned concepts, and attainment of the Most Essential Learning Competencies (MELCs). The results indicated a positive association between effective classroom-based assessment practices and enhanced pupils’ learning outcomes. The study concluded that teachers’ assessment practices play a significant role in improving the quality of instruction and the learning competencies of pupils. The result may serve as basis for the Department of Education in enhancing assessment-based policies, reinforcing teacher professional development, and improving assessment implementation in schools.